2020
DOI: 10.21315/tlsr2020.31.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Construction of A Preliminary Three-Dimensional Structure Simian betaretrovirus Serotype-2 (SRV-2) Reverse Transcriptase Isolated from Indonesian Cynomolgus Monkey

Abstract: Simian betaretrovirus serotype-2 (SRV-2) is an important pathogenic agent in Asian macaques. It is a potential confounding variable in biomedical research. SRV-2 also provides a valuable viral model compared to other retroviruses which can be used for understanding many aspects of retroviral-host interactions and immunosuppression, infection mechanism, retroviral structure, antiretroviral and vaccine development. In this study, we isolated the gene encoding reverse transcriptase enzyme (RT) of SRV-2 that infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Denaturation was a biochemical process that can be used to modify protein structures without causing the breaking of convalent bonds. Proteins can form a zwitter ion structure and have an iso-electric point with the same number of positive and negative ionic charges on the protein (Saepuloh et al 2020;Singh et al 2015), so that in this situation the protein can be denatured. The mechanism of denaturation took place when a substitution reaction occurs between negative and positive ions.…”
Section: Discussionmentioning
confidence: 99%
“…Denaturation was a biochemical process that can be used to modify protein structures without causing the breaking of convalent bonds. Proteins can form a zwitter ion structure and have an iso-electric point with the same number of positive and negative ionic charges on the protein (Saepuloh et al 2020;Singh et al 2015), so that in this situation the protein can be denatured. The mechanism of denaturation took place when a substitution reaction occurs between negative and positive ions.…”
Section: Discussionmentioning
confidence: 99%
“…TM-score and RMSD are widely used to estimate topological structure similarity between predicted model and native protein. TM-score value ranges from 0 to 1, a higher value indicates higher structural match (Saepuloh et al 2020). The analogy with B. subtilis PhoD (2YEQ) showed their similarity as most ARJ 47 partial PhoD structures were overlapping.…”
Section: Discussionmentioning
confidence: 99%
“…An additional response for an interesting study is a characterization of its pathogen compared to NHP was suggested to be performed in future research, such as that performed in a previous study. 7 …”
Section: Dear Editormentioning
confidence: 99%